Maculopapular drug eruption in a patient with human immunodeficiency virus (HIV) infection, wasting syndrome and pulmonary tuberculosis: A case report: English - Oktavriana, Triasari; Febrianto, Bobby; Hanif, Ihsan; Arrosyid, Azhar; Kamilah, Lian; Heryadi, Fanny Fauziyyah; Kariosentono, Harijono (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
Maculopapular drug eruption (MDE) is the most typical type of hypersensitivity reaction. Patients with human immunodeficiency virus (HIV) infection may develop some complications, including wasting syndrome, contributing to immune system dysregulation. The late stage of HIV infection increases the risk of pulmonary tuberculosis (TB), in which the administration of anti-tuberculosis drugs (ATD) often induces drug eruptions. A 41-year-old man complained of itchy skin rash on his hands, body, and feet. The rash appeared after a streptomycin injection on the 9th day, accompanied by complaints of fever, weakness, dizziness, and chronic cough followed by fever at night. The patient was treated and diagnosed with a new case of pulmonary TB; and he also received first-line ATD. The streptomycin injection was given because systemic manifestation still appeared. The researchers diagnosed the patient with HIV infection with wasting syndrome. He was hospitalized and given methylprednisolone injection, paracetamol infusion, omeprazole injection, oral cetirizine, and moisturizer. After that, clinical improvement occurred, and he was discharged on the fourth day. Patients with HIV infection often develop MDE. Clinical manifestations of maculopapular drug eruption are generally mild without systemic complaints; however, in certain conditions, such as HIV infection with wasting syndrome, more severe systemic symptoms can appear due to excess secretion of several proinflammatory cytokines. Several studies have also reported an increased incidence of maculopapular drug eruption caused by first-line anti-HIV drugs, especially in patients with HIV infection.